Management accounting revolution developed and developing country - Pratheepkanth, P. (University of Jaffna, 2018)
The main aim of this paper is to analyse existing literature (1960 -2016) on management accounting revolution by firms in a comparative perspective to see whether any differences between developed and developing countries context. The significant role that management accounting practices play in corporate finance is well established by reams of research articles. The study reveals that there are clear limitations to the literature review, it suggests that a majority of management accounting practices’ studies are focused on developed markets and that there is a scarcity of serious analyses of the situation in emerging markets.
Keywords: Developed countries; Developing countries; Literature review; Management accounting practices